Soluble PD-L1 is associated with local and systemic inflammation markers in primary and secondary brain tumours. Issue 6 (12th November 2020) - Mair, Maximilian J; Pajenda, Sahra; Ilhan-Mutlu, Aysegül; Steindl, Ariane; Kiesel, Barbara; Widhalm, Georg; Dieckmann, Karin; Feldmann, Katharina; Hainfellner, Johannes; Marosi, Christine; Müllauer, Leonhard; Wagner, Ludwig; et al.
Abstract : Background: Immune-modulatory treatments have so far shown limited clinical activity in primary brain tumours. We aimed to investigate soluble programmed death receptor ligand 1 (sPD-L1) as systemic inflammation parameter in patients with brain tumour. Methods: EDTA plasma was collected from 81 glioma (55 glioblastoma (GBM), 26 lower-grade glioma (LGG)), 17 meningioma and 44 brain metastasis (BM) patients and 24 controls. sPD-L1 concentrations were determined by ELISA. Correlations with the local tumour microenvironment were assessed by immunohistochemical analysis for PD-L1, CD3 and CD8. Results: sPD-L1 was detected in 62 out of 166 (37.7%) patients (glioma: 41/81, 50.6%; meningioma: 5/17, 29.4%; BM: 7/44, 15.9%; controls: 9/24, 37.5%; p=0.002). sPD-L1 concentrations were lower in BM than in LGG (p=0.003) or GBM (p<0.001). Membranous PD-L1 expression on tumour cells was not associated with sPD-L1 concentrations (p=0.953). sPD-L1 concentration was inversely correlated with the density of CD8+ (r=−0.713, p=0.001) and CD3+ (r=−0.484, p=0.042) tumour-infiltrating lymphocytes in LGG. sPD-L1 is correlated with neutrophil counts (r=−0.318, p=0.045) and C reactive protein levels (r=−0.363, p=0.008) in GBM. sPD-L1+ patients had longer overall survival in GBM (p=0.006) and worse OS in LGG (p=0.028). Conclusions: sPD-L1 is detectable in a fraction of patients with brain tumour. Although it is not correlated with tissue PD-L1 expression, correlations with other local and systemic inflammation parameters could be detected in LGG and GBM.